2005
DOI: 10.1007/s00018-005-4486-8
|View full text |Cite
|
Sign up to set email alerts
|

The structural and mechanistic basis for recycling of Rab proteins between membrane compartments

Abstract: Rab proteins are members of the Ras superfamily of GTPases and are key regulators of intracellular vesicular transport. They undergo a cycle of GTPase activity, and this activity is interconnected to a cycle of reversible attachment to membranes. This cycle is mediated by geranylgeranylation of (usually) two C-terminal cysteines, which in turn is effected by Rab geranylgeranyltransferase in concert with REP (Rab escort protein). After delivery to their respective membranes, Rabs are activated by replacement of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
109
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(115 citation statements)
references
References 55 publications
4
109
0
2
Order By: Relevance
“…Depolarization-induced Ca 2ϩ influx activates GTP cleavage by membrane-bound Rab3a, followed by the retrieval of GDP-Rab3a by a GDI⅐Hsp90 complex (20,47). The ␣-syn⅐Rab3a complex raised the possibility that the guanine nucleotide-dependent Rab3a conformation may also influence ␣-syn distribution.…”
Section: Discussionmentioning
confidence: 99%
“…Depolarization-induced Ca 2ϩ influx activates GTP cleavage by membrane-bound Rab3a, followed by the retrieval of GDP-Rab3a by a GDI⅐Hsp90 complex (20,47). The ␣-syn⅐Rab3a complex raised the possibility that the guanine nucleotide-dependent Rab3a conformation may also influence ␣-syn distribution.…”
Section: Discussionmentioning
confidence: 99%
“…The interaction between VPS35/29/26 and Rab7 is substoichiometric, which is consistent with a transient and/or dynamic interaction. Mass spectrometric analysis of the large-scale native immunoprecipitations confirmed that the VPS35/29/26 complex interacts with Rab7 and also indicated that the interaction is likely to be direct, because the only other proteins that were detected in the GFP-Rab7 immunoprecipitation lane were Rab escort protein-1 and GDI-1 and GDI-2, both of which are involved in maintaining the cytosolic Rab7 in a soluble form (Goody et al, 2005). We did not observe a band corresponding to VPS29 in the native immunoprecipitation samples, possibly because the silver stain used to visualise the bands does not stain the VPS29 protein.…”
Section: Discussionmentioning
confidence: 87%
“…This mechanism is crucially different for hGBP1 and resembles that of N-terminally myristoylated Arf proteins (36). Human GBP1 F attaches to the membrane upon GTP binding and leaves the membrane as a soluble protein when no more GTP is available, obviously not requiring any helper protein for positioning its farnesyl anchor inaccessible for other interaction partners (like the membrane) as is the case for small Ras-like Rho and Rab GTPases (35). Thus, we report that the accessibility of an isoprenyl anchor from a GTP-binding protein is exclusively controlled by the associated nucleotide.…”
Section: Discussionmentioning
confidence: 99%
“…Many examples of Ras-like proteins show nucleotide-dependent shuttling between various membrane compartments, e.g., the GTP-binding and hydrolysis-driven function of Rab proteins is the traveling between organelles and thereby directing the transport of cargo. These cycles of membrane binding and dissociation are facilitated by specific helper proteins [guanine-nucleotide dissociation inhibitors (GDIs)], which take up the isoprenyl anchor in a binding pocket to enable the GTP-binding protein to leave the membrane and travel through the cytosol (35). This mechanism is crucially different for hGBP1 and resembles that of N-terminally myristoylated Arf proteins (36).…”
Section: Discussionmentioning
confidence: 99%